2020
DOI: 10.1038/s41467-020-17988-7
|View full text |Cite
|
Sign up to set email alerts
|

Geometric principles underlying the proliferation of a model cell system

Abstract: Many bacteria can form wall-deficient variants, or L-forms, that divide by a simple mechanism that does not require the FtsZ-based cell division machinery. Here, we use microfluidic systems to probe the growth, chromosome cycle and division mechanism of Bacillus subtilis L-forms. We find that forcing cells into a narrow linear configuration greatly improves the efficiency of cell growth and chromosome segregation. This reinforces the view that L-form division is driven by an excess accumulation of surface area… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 70 publications
(119 reference statements)
5
44
2
Order By: Relevance
“…This finding suggests that contact between cells and solids or mechanical stress is essential for the interconversion between walled cells and the L-form, as well as for proliferation of the latter. The role of mechanical stress is also supported by the observation that elongated L-form cells grown in a narrow channel assumed a spherical shape when they were placed in a wide channel ( Wu et al, 2020 ). This result may explain why L-form cells, absent from suspensions containing PenG and L-form colonies, appear inside the plate rather than on its surface ( Joseleau-Petit et al, 2007 ).…”
Section: Discussionmentioning
confidence: 86%
“…This finding suggests that contact between cells and solids or mechanical stress is essential for the interconversion between walled cells and the L-form, as well as for proliferation of the latter. The role of mechanical stress is also supported by the observation that elongated L-form cells grown in a narrow channel assumed a spherical shape when they were placed in a wide channel ( Wu et al, 2020 ). This result may explain why L-form cells, absent from suspensions containing PenG and L-form colonies, appear inside the plate rather than on its surface ( Joseleau-Petit et al, 2007 ).…”
Section: Discussionmentioning
confidence: 86%
“…In particular, some L-forms undergo an irregular cell division mechanism, termed "extrusion-resolution," involving extrusion of excess membrane, followed by resolution of the extrusion into connected units (Errington, 2017). This mechanism requires excess membrane synthesis (Mercier et al, 2013), does not require FtsZ or FtsA (Leaver et al, 2009), and is suppressed by confinement in submicron microfluidic channels (Wu et al, 2020). Our observations suggest the extrusion-resolution model is relevant to propagation of JCVI-syn3.0 and related genomically minimized strains, and our study highlights a wide range of morphological dynamics that can occur without shear flow.…”
Section: Morphological Dynamics Intrinsic To Cells Revealed By Microfluidic Chemostatsmentioning
confidence: 99%
“…Furthermore, the initial segregation of ori in these expanded cells (Japaridze et al, 2020) oriented randomly until the replication of chromosomal mass recovered a level of confinement needed to direct the oris toward the cell poles (Figure 5B). Other studies showed that cell-wall-less cells (socalled L-form cells) exhibited typical segregation defects, such as more randomly oriented nucleoids that physically separated from one another only rarely, while successful segregation could be recovered by confining these cells into synthetic channels of cell-sized dimensions (Wu et al, 2019b(Wu et al, , 2020 (Figure 5C). The mere restoration of confinement similar to that imposed by the cell wall thus was able to determine success in segregation, which clearly shows that physics effects are at play, since the biological content of the cells was the same in both shapes.…”
Section: Entropy As a Segregating Forcementioning
confidence: 98%
“…Red arrowheads point at examples of orthogonally and perpendicularly oriented nucleoids relative to the cellular long axis. From Wu et al (2020). (D) Re-distribution of two chromosomes in an elongated E. coli cell.…”
Section: Entropy As a Segregating Forcementioning
confidence: 99%